Pengaruh Tingkat Inflasi, Ekspor, dan BI-7 Day Repo Rate terhadap Cadangan Devisa Negara Indonesia Tahun 2020-2022 - Budi, Muchammad Aris Setia; Setiawati, Ratna Dewi; Putri, Rizki Ananda; Rifai, Muhammad Agus (Ikatan Da'i Indonesia, 2024)
influence between the BI-7 Day Repo Rate, Exports, and Inflation Rate on Indonesia’s Foreign Exchange Reserves in 2020-2022. There are 36 data samples that are the object of research. Indonesia’s foreign exchange reserves are the dependent variable while exports, BI-7 Day Repo Rate, and inflation rate are the independent variables. Before conducting various linear regression analysis tests to see how the independent variables impact the dependent variable, the researchers first conducted a classical assumption test. The results showed that Indonesia’s foreign exchange reserves are affected by exports, BI-7 Day Repo Rate, and inflation rate. However, exports have a positive and significant impact on Indonesia’s foreign exchange reserves, while inflation and BI-7 Day Repo Rate have a negative and significant impact on foreign exchange reserves.